7z+2=-6

Simple and best practice solution for 7z+2=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z+2=-6 equation:


Simplifying
7z + 2 = -6

Reorder the terms:
2 + 7z = -6

Solving
2 + 7z = -6

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 7z = -6 + -2

Combine like terms: 2 + -2 = 0
0 + 7z = -6 + -2
7z = -6 + -2

Combine like terms: -6 + -2 = -8
7z = -8

Divide each side by '7'.
z = -1.142857143

Simplifying
z = -1.142857143

See similar equations:

| -7+2=6 | | 9x+16-6x=10-2x-19 | | 2p-3=p-5 | | 5a-16=25 | | v^2-10v+16= | | 4w-3x-y-5w+18x-7y= | | -6+[25+(-12)]=43 | | X^2+100+60-3x+30-4x=180 | | -6+[25+(-12)]=31 | | -13+2x=-52+13 | | -6+[25+(-12)]=7 | | -6+[25+(-12)]=19 | | 4=5+2x | | 5x+17-4x=-2-10 | | X/Y=7/11 | | 3x^2-(3m-2)x-(3m+1)=0 | | 1/3*1/3*1/3*1/3*a*a*b*b*c | | 5x-3y=106 | | 16+7yi=8x+i | | x-6=3(2x) | | f-5-3f=7 | | 2x+(x+1)=2 | | 2(4w+9)/4=-10 | | 5x/6-3/2=x/3 | | 0.5(7y+1)-3=8 | | 5(f-1)=25 | | 15m+2n-6m+8n= | | 15x^2+42x=9 | | (1/7)y-4=-18 | | 66=x/-2 | | 9-x=3-5x | | 0=276x^2+2x-0.25 |

Equations solver categories